Case report study of the first five COVID-19 patients treated with remdesivir in France. (September 2020) - Dubert, Marie; Visseaux, Benoit; Isernia, Valentina; Bouadma, Lila; Deconinck, Laurène; Patrier, Juliette; Wicky, Paul-Henri; Le Pluart, Diane; Kramer, Laura; Rioux, Christophe; Le Hingrat, Quentin; Houhou-Fidouh, Nadhira; et al.
Highlights: Remdesivir has been found to be potent in vitro inhibitor of RNA viruses including SARS-CoV-2, but its in vivo potency is still under investigation. This study report the clinical and biological features of five patients hospitalized with COVID-19 and treated with remdesivir for compassionate use. For two patients, viral loads in nasopharyngeal samples decreased, despite active replication in the lower respiratory tract area. The treatment had to be interrupted in four of the five patients, because of ALT elevation and/or renal failure. Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been identified as the virus responsible for the coronavirus disease 2019 (COVID-19) outbreak worldwide. Data on treatment are scare and parallels have been made between SARS-CoV-2 and other coronaviruses. Remdesivir is a broad-spectrum antiviral with efficient in vitro activity against SARS-CoV-2. Evidence of clinical improvement in patients with severe COVID-19 treated with remdesivir is controversial. The aim of this study was to describe the clinical outcomes and virological monitoring of the first five COVID-19 patients admitted to the intensive care unit of Bichat-Claude Bernard University Hospital, Paris, France, for severe pneumonia related to SARS-CoV-2 and treated with remdesivir. Quantitative reverse transcription PCR was used to monitor SARS-CoV-2 in blood plasma and the lower and upper respiratory tract. Among the five patients treated, two needed mechanical ventilation and one needed high-flow cannula oxygen. A significant decrease in SARS-CoV-2 viral load in the upper respiratory tract was observed in most cases, but two patients died with active SARS-CoV-2 replication in the lower respiratory tract. Plasma samples were positive for SARS-CoV-2 in only one patient. Remdesivir was interrupted before the initialy planned duration in four patients, two because of alanine aminotransferase elevations (3 to 5 normal range) and two because of renal failure requiring renal replacement. This case series of five COVID-19 patients requiring intensive care unit treatment for respiratory distress and treated with remdesivir, highlights the complexity of remdesivir use in such critically ill patients.